Lactobacillus rhamnosus GG supplementation on eradication rate and dyspepsia in Helicobacter pylori infection treated with three-in-one bismuth quadruple therapy - Marinelli, Paride; Scalese, Giulia; Covelli, Antonio; Ruffa, Andrea; Bedetti, Giorgio; Bruno, Giovanni; Severi, Carola (Frontiers in Microbiology, 2022)
Helicobacter pylori (Hp)-related dyspepsia has been related to gastroduodenal dysbiosis. The role of probiotics supplementation in the clinical management of Hp infection has been the object of several studies in terms of improvement of efficacy and tolerability of eradication treatments but data on their effects on post-eradication dyspepsia outcomes are lacking. The aim of the present study was to evaluate the influence of Lactobacillus Rhamnosus GG (LGG) supplementation to Bismuth-quadruple therapy (BQT) in the clinical management of Hp-related infection both in terms of efficacy and tolerability and persistence of post-treatment dyspepsia. 164 patients (121 females) Hp-positive adult patients were enrolled in this pilot study and assigned to 2 different treatment regimens: Group A received BQT for 10 days (3 capsules qid, IPP bid); Group B received BQT for 10 days in combination with 6x109CFU LGG (ATCC53103) taken for 24 days (7 days before, 10 days during and 7 days after therapy). Eradication was assessed after 45 days using 13C-urea breath test. Dyspepsia, distinguished into Postprandial Distress Syndrome (PDS) and Epigastric Pain Syndrome (EPS), was assessed at the time of enrolment and 6 months after eradication. 98 patients were enrolled in group A and 66 patients in Group B. At the enrollment, dyspepsia was present in 76.5% in the group A and 86.5% in the group B. No significant differences were observed in eradication rate between the 2 groups, both in ITT analysis (82.3% vs 75.0%) and PP analysis (95% vs 96%) and in the presence of side effects during the treatment (70.6% vs 65.4% ). At 6-month after eradication of Hp infection, the persistence of dyspepsia was statistically higher in patients of Group A than Group B (38.8% vs 16.1% ; p=0.032). The positive influence of LGG supplementation in improving dyspepsia post-eradication resulted statistically more effective in PDS dyspepsia, whose remission was 41.7% in group A and 84% of group B patients (p=0.011). In conclusion, LGG supplementation during Hp eradication therapy, even if not affecting eradication rates and therapy-related side effects. significantly impacts on the remission of dyspepsia.